The Prevalence and Awareness of Cardiometabolic Risk Factors in Southern Chinese Population with Coronary Artery Disease - Li, Xinrui (Hindawi Publishing Corporation, 2013)
Background. Cardiometabolic risk factors significantly accelerate the progression of coronary artery disease (CAD); however, whether CAD patients in South China are aware of the prevalence of these risk factors is not clear yet. Methods. The study consisted of 2312 in-admission CAD patients from 2008 to 2011 in South China. Disease history including hypertension, dyslipidemia, and diabetes was relied on patients' self-reported records. Physical and clinical examinations were tested to assess the real prevalence of the cardiometabolic risk factors. Results. 57.9% of CAD patients had more than 3 cardiometabolic risk factors in terms of the metabolic syndrome. The self-known and real prevalence of hypertension, diabetes, and dyslipidemia were 56.6%, 28.3%, and 25.1% and 91.3%, 40.9%, and 92.0%, respectively. The awareness rates were 64.4%, 66.3%, and 28.5% for hypertension, diabetes, and dyslipidemia. The prevalence of cardiometabolic risk factors was significantly different among gender and among disease status. Conclusions. Most CAD patients in South China had more than three cardiometabolic risk factors. However, the awareness rate of cardiometabolic diseases was low, especially for dyslipidemia. Strategies of routine physical examination programs are needed for the early detection and treatment of cardiometabolic risk factors in order to prevent CAD progression and prognosis.